Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1016/0014-5793(90)80143-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a molten globule state as a general intermediate in protein folding

Abstract: The folding of globular proteins occurs through intermediate states whose characterisation provides information about the mechanism of folding. A major class of intermediate,states is the compact 'molten globule', whose characteristics have been studied intensively in those conditions in which it is stable (at acid pH, high temperatures and intermediate concentrations of strong denaturants). In studies involving bovine carbonic anhydrase, human a-lact-albumin, bovine /3-lactoglobulin, yeast phosphoglycerate ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
459
1
5

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 676 publications
(492 citation statements)
references
References 27 publications
25
459
1
5
Order By: Relevance
“…This distribution has been actually observed for equilibrium urea-induced unfolding of myoglobin [18] and of bovine serum albumin [19] at 25°C. The U -> MG transition usually takes place in a few seconds [4,7]. However, this transition takes much more time for some proteins in cool Gdm-HCI solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This distribution has been actually observed for equilibrium urea-induced unfolding of myoglobin [18] and of bovine serum albumin [19] at 25°C. The U -> MG transition usually takes place in a few seconds [4,7]. However, this transition takes much more time for some proteins in cool Gdm-HCI solutions.…”
Section: Resultsmentioning
confidence: 99%
“…It is almost as compact as the native state (N), has a pronounced secondary structure and differs from N mainly by the absence of ~ight packing of side chains in the protein core and by a substantial increase of fluctuations [1][2][3][4]. The molten globule state (MN) accumulates during the renaturation of globular proteins from the fully unfolded state (U) [1][2][3][4][5][6][7][8] and therefore may play a universal role in protein folding [7]. It has been also suggested [9] and shown experimentally that the molten globule is trapped by Gro-EL chaperons ( [10] and unpublished data of G.V.…”
Section: Introductionmentioning
confidence: 99%
“…The species (observed at equilibrium for a large number of proteins under mild denaturing conditions with properties of partially-folded states) made possible the study in real-time scale experiments. Such intermediates from different proteins of different structure types have some common characteristics, and are termed as "molten globule" to emphasize the possible occurrence of such an intermediate as a general physical state of globular proteins (Ptitsyn et al, 1990;Harding et al, 1991;Arai and Kuwajima, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Side-chain packing may also be important to the kinetics of folding. Ptitsyn (1987) and Ptitsyn et al (1990) is critical. Rey and Skolnick (1993) have shown that the addition of model side chains to a model main chain in a computer simulation of protein folding reduces the number of pathways that lead to the native state, and Handel et al (1993) have shown that it is not easy to design sequences that can fold to conformations with immobilized side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Side-chain packing may also be important to the kinetics of folding. Ptitsyn (1987) and Ptitsyn et al (1990) have suggested that the slow rate of protein folding may be due to the process of packing core side chains. Recent computer simulation and protein design results also suggest that the packing of side chains Reprint requests to: Ken A. Dill, Department of Pharmaceutical Chemistry, Box 1204, University of California, San Francisco, California 94143-1204; e-mail: dill@maxwell.ucsf.edu.…”
mentioning
confidence: 99%